Induction chemotherapy with docetaxel/cisplatin/5-fluorouracil followed by randomization to two cisplatin-based concomitant chemoradiotherapy schedules in patients with locally advanced head and neck cancer (CONDOR study) (Dutch Head and Neck Society 08-01): A randomized phase II study. (January 2016) - Driessen, C.M.L.; de Boer, J.P.; Gelderblom, H.; Rasch, C.R.N.; de Jong, M.A.; Verbist, B.M.; Melchers, W.J.G.; Tesselaar, M.E.T.; van der Graaf, W.T.A.; Kaanders, J.H.A.M.; van Herpen, C.M.L.
Abstract: Purpose: To study the feasibility of induction chemotherapy added to concomitant cisplatin-based chemoradiotherapy (CRT) in patients with locally advanced head and neck cancer (LAHNC). Patients and methods: LAHNC patients were treated with 4 courses of docetaxel/cisplatin/5-fluorouracil (TPF) followed by randomization to either cisplatin 100 mg/m 2 with conventional radiotherapy (cis100 + RT) or cisplatin 40 mg/m 2 weekly with accelerated radiotherapy (cis40 + ART). Primary endpoint was feasibility, defined as receiving ≥90% of the scheduled total radiation dose. Based on power analysis 70 patients were needed. Results: 65 patients were enrolled. The data safety monitoring board advised to prematurely terminate the study, because only 22% and 41% (32% in total) of the patients treated with cis100 + RT (n = 27) and cis40 + ART (n = 29) could receive the planned dose cisplatin during CRT, respectively, even though the primary endpoint was reached. Most common grade 3–4 toxicity was febrile neutropenia (18%) during TPF and dehydration (26% vs 14%), dysphagia (26% vs 24%) and mucositis (22% vs 57%) during cis100 + RT and cis40 + ART, respectively. For the patients treated with cis100 + RT and cis40 + ART, two years progression free survival and overall survival were 70% and 78% versus 72% and 79%, respectively. Conclusion: After TPF induction chemotherapy, cisplatin-containing CRT is not feasible in LAHNC patients, because the total planned cisplatin dose could only be administered in 32% of the patients due to toxicity. However, all but 2 patients received more than 90% of the planned radiotherapy. Clinical Trials Information:NCT00774319 . Highlights: Phase II study of TPF induction chemotherapy followed by cisplatin-containing chemoradiotherapy. We studied feasibility of these treatment schedules. Cisplatin-containing chemoradiotherapy is not feasible after TPF induction. Only a small group of patients could complete all treatment.